Difficult treatment of superinfected with pseudomonas aeruginosa verrucous leishmaniasis - Di Martino, Beatriz; Valiente Rebull, Zulema Alexandra Celeste; Re Dominguez, Maria Lorena; Bolla, Lourdes; Rodriguez Masi, Mirtha; Knopfelmacher, Oilda (Medicina Clínica y Social, 2025)
Leishmaniasis is an endemic pathology produced by protozoans of the genus Leishmania, of which there are different species, which can affect skin, mucous membranes and /or viscera. We report the case of a 53-year-old male with erythematous violaceous plaque with verrucous borders, net limits in the thorax and back of 10 years of evolution, with a diagnosis of verrucous leishmaniasis, in whom systemic treatment was made with two different drugs and cryotherapy, with excellent result.